Problem solving and learning for a humanoid robot - Choi, D.; Kim, K.; Kim, D.; You, B.-J. (2011 IEEE International Conference on Robotics and Biomimetics, ROBIO 2011, 2011)
Based on our previous work that integrated a cognitive architecture, Icarus, and a humanoid robot, Mahru, we extend our use of the architecture to higher-level capabilities of problem solving and learning. During this process, we found the need to address a known limitation of ICARUS's problem solver. An extension is made to allow handling of underspecified goals in the system, and we demonstrate this new ability in a blocks world task that involves alphabet writing with several identical blocks. ？ 2011 IEEE.